Utilización de balanceado más forraje de botón de oro (Tithonia diversifolia) en el engorde de cuyes peruanos mejorados (Cavia porcellusl.) Mocache, 2013. - Chávez Araujo, Byron Fabricio (2013)
The research was carried out inthe Fifth “PHASE", located at kilometer8ViaQuevedo-Mocacheprovince ofLosRíos.The investigationlasted56 days. Theobjectives were to determine the productive parameters(feed intake, weight gain and production)of guinea pigsfedmoreforagebalancedbuttercup andestablish the profitability of the treatments. In the present investigationa complete random design(DCA) with 5 replicationsand 2guinea pigsforexperimentalunit wasapplied. Todetermine differencesbetween treatmentsmean for each period, the test ofTukeymultiple ranges(P≤0.05) was applied. Thehigher feed intake, body weight and weight gainregistrationas treatmentT2.Increased consumption ofbalanced and feed conversionwas recorded by treatmentT1, theweight ofthe channel is not influenced bythetropical forageshrub in fatteningguinea pigs, increased consumption of forage, carcassyield and profitabilitywas recorded byT4. Usethebuttonsupplementedwith 20go goldbalanced pelletedguinea pigskinfattening because it allowsin creasedforage intake, carcass yieldand profitability.Assessingtropicalshrub forage(mulberry caracaandbuttercup) in different period’s ofcourt